Marked, persistent basophilia in a potbellied pig. Issue 1 (22nd December 2021) - Towns, Taylor Jordan; Tomlinson, Julie; Chamorro, Manuel F.; Lindley, Stephanie E. S.; Graff, Emily C.
Abstract: A 5‐year‐old intact female potbellied pig presented for a 2‐week history of anorexia, lethargy, and intermittent fever. Over 2 months, serial complete blood count evaluations revealed a persistent, progressive, marked basophilia and differential diagnoses included parasitism, hypersensitivity reaction, paraneoplastic response, or basophilic leukaemia. The patient was diagnosed with basophilic leukaemia based on the persistent, marked basophilia and exclusion of other differentials. Due to possible inconsistencies in basophil identification by automated haematology analysers, blood smear examination must be performed to quantify circulating basophils. Diagnosis of basophilic leukaemia is based on light microscopic examination of blood and/or bone marrow and exclusion of other differentials. While basophilic leukaemia is rare in veterinary medicine, it should be considered a differential for a marked, persistent basophilia in any species. This case highlights some of the challenges associated with diagnosing and treating this disorder.